2015
DOI: 10.1371/journal.pone.0130522
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Cytokine Responses in Hidradenitis Suppurativa

Abstract: BackgroundFavorable treatment outcomes with TNF blockade led us to explore cytokine responses in hidradenitis suppurativa (HS).MethodsBlood monocytes of 120 patients and 24 healthy volunteers were subtyped by flow cytometry. Isolated blood mononuclear cells (PBMCs) were stimulated for cytokine production; this was repeated in 13 severe patients during treatment with etanercept. Cytokines in pus were measured.ResultsCD14brightCD16dim inflammatory monocytes and patrolling monocytes were increased in Hurley III p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 24 publications
4
64
1
1
Order By: Relevance
“…A previous study investigating blood monocyte subtypes in HS patients found certain monocyte subtypes increased in Hurley stage III, but low cytokine production from stimulated blood mononuclear cells [35]. Our study found HS to be associated with higher levels of monocytes compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…A previous study investigating blood monocyte subtypes in HS patients found certain monocyte subtypes increased in Hurley stage III, but low cytokine production from stimulated blood mononuclear cells [35]. Our study found HS to be associated with higher levels of monocytes compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…Psoriasis involves systemic inflammatory responses and frequent comorbidities are rheumatological or cardiovascular in nature47. In hidradenitis suppurativa, also known as acne inversa, a devastating skin disorder bearing the characteristics of both auto-inflammatory and auto-immune disorders, histopathology reveals heavy lesional deposits of TNF, IL-1β, IL-23 and IL-17, as well as activation of both CD4 + and CD8 + T cells 48.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Prior studies investigating cytokine profiles in HS patients have shown high levels of proinflammatory cytokines in pus extracted from HS lesions but low cytokine production in peripheral blood mononuclear cells (PBMC) from patients compared to normal controls (Kanni, Tzanetakou et al 2015). This suggests that there is compartmentalized cytokine expression in HS.…”
Section: Discussionmentioning
confidence: 99%